Could Soluble Endothelial Protein C Receptor Levels Recognize SARS-CoV2-Positive Patients Requiring Hospitalization?. Issue 5 (November 2021) - Vassiliou, Alice G.; Keskinidou, Chrysi; Jahaj, Edison; Gallos, Parisis; Zacharis, Alexandros; Athanasiou, Nikolaos; Tsipilis, Stamatios; Mastora, Zafeiria; Dimopoulou, Ioanna; Kotanidou, Anastasia; Orfanos, Stylianos E.
ABSTRACT: Introduction: The endothelial protein C receptor (EPCR) is a protein that regulates the protein C anticoagulant and anti-inflammatory pathways. A soluble form of EPCR (sEPCR) circulates in plasma and inhibits activated protein C (APC) activities. The clinical impact of sEPCR and its involvement in COVID-19 has not been explored. In this study, we investigated whether sEPCR levels were related to COVID-19 patients' requirement for hospitalization. Methods: Plasma sEPCR levels were measured on hospital admission in 84 COVID-19 patients, and in 11 non-hospitalized SARS-CoV2-positive patients approximately 6 days after reported manifestation of their symptoms. Multiple logistic regression analysis was performed to identify potential risk factors for hospitalization and receiver operating characteristic (ROC) curves were generated to assess their value. Results: In our cohort, hospitalized patients had considerably higher sEPCR levels upon admission compared with outpatients [107.5 (76.7–156.3) vs. 44.6 (12.1–84.4) ng/mL; P < 0.0001)]. The ROC curve using hospitalization as the classification variable and sEPCR levels as the prognostic variable generated an area under the curve at 0.845 (95% CI = 0.710–0.981, P < 0.001). Additionally, we investigated the predictive value of sEPCR combined with BMI, age, or D-dimers. Conclusions: In our cohort, sEPCR levels in COVID-19 patients upon hospital admission appear considerably elevated compared with outpatients; this could lead to impaired APC activities and might contribute to the pro-coagulant phenotype reported in such patients. sEPCR measurement might be useful as a point-of-care test in SARS-CoV2-positive patients. Abstract : Supplemental Digital Content is available in the text